2014
DOI: 10.1093/mnras/stu099
|View full text |Cite
|
Sign up to set email alerts
|

Tracing sunspot groups to determine angular momentum transfer on the Sun

Abstract: The goal of this paper is to investigate Reynolds stresses and to check if it is plausible that they are responsible for angular momentum transfer toward the solar equator. We also analysed meridional velocity, rotation velocity residuals and correlation between the velocities. We used sunspot groups position measurements from GPR (Greenwich Photographic Result) and SOON/USAF/NOAA (Solar Observing Optical Network/United States Air Force/National Oceanic and Atmospheric Administration) databases covering the pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 51 publications
13
43
1
Order By: Relevance
“…Another branch might be visible above 50 • , even though the errors are becoming large in that region of latitudes. This type of result is more consistent with Doppler measurements than with sunspot data where Sudar et al (2014) found no stable pattern that resembles torsional oscillations.…”
Section: Solar Rotation Profile and Rotation Velocity Residualssupporting
confidence: 88%
See 4 more Smart Citations
“…Another branch might be visible above 50 • , even though the errors are becoming large in that region of latitudes. This type of result is more consistent with Doppler measurements than with sunspot data where Sudar et al (2014) found no stable pattern that resembles torsional oscillations.…”
Section: Solar Rotation Profile and Rotation Velocity Residualssupporting
confidence: 88%
“…The only notable exception is the bin at 25 • where q ≈ −1500 m 2 s −2 and possibly the bin at 15 • . Sudar et al (2014) found the minimum at the same latitude, but about twice as deep. They also found negative values of q for all latitudes below 35 • .…”
Section: Horizontal Reynolds Stressmentioning
confidence: 78%
See 3 more Smart Citations